2020
DOI: 10.1515/ijamh-2018-0140
|View full text |Cite
|
Sign up to set email alerts
|

Parental decision-making on human papillomavirus vaccination for daughters in Japan

Abstract: BackgroundIn June 2013, the fear of adverse events compelled the government to withdraw its recommendation of the Human papillomavirus (HPV) vaccine.Since then, the rate of vaccination among Japanese girls has dropped dramatically.ObjectiveThis study aims to assess how the Japanese government’s policy change against HPV vaccination influenced the degree to which parents in remote areas in Japan accepted the vaccine for their daughters, and to analyze related factors. MethodsA self-administered questionnaire wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Our integrated health behaviour model offers a novel way of visualizing how these factors are interrelated. We found that perceived sexual inactivity of adolescents (34,(39)(40)(41), insu cient knowledge about vaccination timing, safety and effectiveness (24,(41)(42)(43) and preference for 9vHPV vaccine in uenced parents' individual decision and were consistent with determinants of vaccine hesitancy identi ed from studies conducted in the United States, Kenya and Japan. Furthermore, systemic barriers such as supply shortage, inadequate communication and dissemination of information (40)(41)(42) also contributed to hesitancy.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our integrated health behaviour model offers a novel way of visualizing how these factors are interrelated. We found that perceived sexual inactivity of adolescents (34,(39)(40)(41), insu cient knowledge about vaccination timing, safety and effectiveness (24,(41)(42)(43) and preference for 9vHPV vaccine in uenced parents' individual decision and were consistent with determinants of vaccine hesitancy identi ed from studies conducted in the United States, Kenya and Japan. Furthermore, systemic barriers such as supply shortage, inadequate communication and dissemination of information (40)(41)(42) also contributed to hesitancy.…”
Section: Discussionsupporting
confidence: 75%
“…We found that caregivers who chose not to delay vaccination were more likely to have communicated with friends or family members. Similarly, studies in Japan found that high social support was related to greater parental acceptance (42,43).…”
Section: Discussionmentioning
confidence: 89%
“…20 Similar results are supported by other studies, 21 including regarding mothers' perception of the HPV vaccine and their intentions to have their daughters vaccinated. 22,23 Acceptance of the HPV vaccine was higher among parents working in healthcare, who were knowledgeable about the HPV vaccine and cervical cancer. 22 Clear and unbiased information about HPV, cervical cancer, and the HPV vaccine, along with proactive recommendation by the MHLW, could thus be key determinants of parents' and female adolescents' willingness to accept HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Acceptance of the HPV vaccine was higher among parents working in healthcare, who were knowledgeable about the HPV vaccine and cervical cancer. 22 Clear and unbiased information about HPV, cervical cancer, and the HPV vaccine, along with proactive recommendation by the MHLW, could thus be key determinants of parents' and female adolescents' willingness to accept HPV vaccination. This is especially true given that although trust in doctors and nurses in Japan is generally high, confidence in vaccines is low, underscoring wider issues relating to trust in the government and their policies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation